2012
DOI: 10.5032/jae.2012.04141
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of School Culture on Environmental Education Integration: A Case Study of an Urban Private School System

Abstract: As a discipline, environmental education (EE) has been criticized for lacking empirical evidence on the behavioral outcomes of its programs. While the behavioral outcomes of EE activities are often associated with the youth learner, teachers are one target audience of EE training programs who have received increasing attention with regards to behavior change. Previous research has identified numerous barriers to teaching EE in the classroom. Barriers include a lack of natural spaces to conduct EE activities, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…As a teacher believes others think they should use gardens in their curriculum, their intent in their current situation should increase. Therefore, if an administrator would like for more teachers to use school gardens, they could make a first step by making a more conducive environment with positive attitudes toward teachers using gardens (Shumacher, Fuhrman, & Duncan, 2012).…”
Section: Objectivementioning
confidence: 99%
“…As a teacher believes others think they should use gardens in their curriculum, their intent in their current situation should increase. Therefore, if an administrator would like for more teachers to use school gardens, they could make a first step by making a more conducive environment with positive attitudes toward teachers using gardens (Shumacher, Fuhrman, & Duncan, 2012).…”
Section: Objectivementioning
confidence: 99%
“…As curriculum needs and delivery models continue to evolve to meet the needs of 21 st century learners, so will the concepts and lessons taught in the secondary agriculture classroom. Shumacher, Fuhrman, and Duncan (2012), reported environmental education should be proactive in the curriculum. Therefore, the continuing education of secondary teachers must possess components to meet these needs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Vallera and Bodzin (2016) reported that although agriculture has in most part been removed from the secondary curriculum, science and environmental education is being reincorporated for greater student development in science education. The reintegration of environmental science content is supported by teachers, parents, and administration through open curriculum exploration, collaboration, and integration within existing content areas (Shumacher, et al, 2012). The efforts to reincorporate environmental science as a component of agricultural education will require specialized technical training for secondary agricultural education students.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Environmental education and career and technical agricultural education often operate in both settings and share many similarities. Although traditionally not explored in the career and technical agricultural education research base, Shumacher et al (2012) encouraged synergy between the disciplines because both are rooted in experiential learning, are often place-based, and capitalize on using the teaching environment as a conduit for student learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agricultural educators and environmental educators have much in common. Both types of educators often work in outdoor environments and other environments which are unfamiliar to their learners (Shumacher, Fuhrman, & Duncan, 2012). Both use instructional techniques to move learners from awareness of environmental issues to taking the necessary action to address such issues.…”
Section: Introductionmentioning
confidence: 99%